Essential Oils from Plants: A Review on Eco-Friendly Mosquito Repellents - Ganesan, Pathalam; Rajan, Samuel; Magesh, Daniel; Williamraja, Tharsiusraja; Paulraj, Michael Gabriel; Ignacimuthu, Savarimuthu (International Journal of Scientific Research in Biological Sciences, 2019)
Essential oils from medicinal plants are widely used all over the world as insect repellents as they are highly safe and beneficial to environment with least ill-effects on animal and public health. Electronic databases including Science direct, PubMed, Scopus, Cochrane library and Scifinder were searched for papers on essential oils from plants with mosquito repellent efficacy. Ethnobotany, phytochemistry and repellent efficacy of plant essential oils were also discussed in this review. This review discusses in detail the mosquito-repellent plant essential oils which would be helpful in effective formulation of different essential oils for efficient control of mosquitoes, thus vector-borne diseases and for pharmacological studies, i.e., drug designing. This review would assist in finding studies on different mosquito-repellent plant essential oils at one stop, since it summarizes a large number of reports on essential oils.